Analisis Perbandingan Strategi Reuse Service dalam Implementasi Service-Oriented Architecture (SOA) untuk Efisiensi Proyek Teknologi Informasi - Ismawan, Andika Noor; Hamdani, Bagus Rosyid; Ramadan, Sahri; Egnel, Unique Scovi; Komul, Theodora Maria Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid advancement of digital technology necessitates the adoption of efficient and sustainable system development strategies. This study aims to conduct a comparative analysis of four reuse service approaches within the framework of Service-Oriented Architecture (SOA), namely API & Service Standardization, Microservices Architecture, API-First Development, and Enterprise Service Bus (ESB). The research method employed is a literature review of recent scholarly sources, along with an evaluation of the effectiveness of each approach in terms of time efficiency, cost, and resource utilization. The findings indicate that each strategy possesses distinct characteristics and contextual advantages, with the API-First approach deemed the most flexible in supporting service integration and modular system development. Based on these findings, it is recommended that the selection of reuse strategies be aligned with organizational needs and the complexity of the systems being developed.